The Interplay of Renin-Angiotensin System and Toll-Like Receptor 4 in the Inflammation of Diabetic Nephropathy - Qi Feng; Dongwei Liu; Yanfang Lu; Zhangsuo Liu (Journal of Immunology Research)
Diabetic nephropathy (DN) is one of the most serious chronic kidney diseases and the major cause of end-stage renal failure worldwide. The underlying mechanisms of DN are complex and required to be further investigated. Both innate immunity and renin-angiotensin system (RAS) play critical roles in the pathogenesis of DN. Except for traditional functions, abnormally regulated RAS has been proved to be involved in the inflammatory process of DN. Toll-like receptor 4 (TLR4) is the most deeply studied pattern recognition receptor in the innate immune system, and its activation has been reported to mediate the development of DN. In this review, we aim at discussing how dysregulated RAS affects TLR4 activation in the kidney that contributes to the exploration of the pathogenesis of DN. Understanding the interplay of RAS and TLR4 in inducing the progression of DN may provide new insights to develop effective treatments.